Effects of chronic l-theanine administration in patients with major depressive disorder: an open-label study. Issue 2 (11th July 2016) - Hidese, Shinsuke; Ota, Miho; Wakabayashi, Chisato; Noda, Takamasa; Ozawa, Hayato; Okubo, Tsutomu; Kunugi, Hiroshi
Abstract : Objective: l -theanine, an amino acid uniquely contained in green tea ( Camellia sinensis ), has been suggested to have various psychotropic effects. This study aimed to examine whetherl -theanine is effective for patients with major depressive disorder (MDD) in an open-label clinical trial. Methods: Subjects were 20 patients with MDD (four males; mean age: 41.0±14.1 years, 16 females; 42.9±12.0 years).l -theanine (250 mg/day) was added to the current medication of each participant for 8 weeks. Symptoms and cognitive functions were assessed at baseline, 4, and 8 weeks afterl -theanine administration by the 21-item version of the Hamilton Depression Rating Scale (HAMD-21), State-Trait Anxiety Inventory (STAI), Pittsburgh Sleep Quality Index (PSQI), Stroop test, and Brief Assessment of Cognition in Schizophrenia (BACS). Results: HAMD-21 score was reduced afterl -theanine administration ( p =0.007). This reduction was observed in unremitted patients (HAMD-21>7; p =0.004) at baseline. Anxiety-trait scores decreased afterl -theanine administration ( p =0.012) in the STAI test. PSQI scores also decreased afterl -theanine administration ( p =0.030) in the unremitted patients at baseline. Regarding cognitive functions, response latency ( p =0.001) and error rate ( p =0.036) decreased in the Stroop test, and verbal memory ( p =0.005) and executive function ( p =0.016) were enhanced in the BACS test afterl -theanine administration. Conclusion: Our study suggests that chronic (8-week)l -theanine administration is safe and has multiple beneficial effects on depressive symptoms, anxiety, sleep disturbance and cognitive impairments in patients with MDD. However, since this is an open-label study, placebo-controlled studies are required to consolidate the effects.